2022
DOI: 10.3390/rs14215515
|View full text |Cite
|
Sign up to set email alerts
|

Computational Machine Learning Approach for Flood Susceptibility Assessment Integrated with Remote Sensing and GIS Techniques from Jeddah, Saudi Arabia

Abstract: Floods, one of the most common natural hazards globally, are challenging to anticipate and estimate accurately. This study aims to demonstrate the predictive ability of four ensemble algorithms for assessing flood risk. Bagging ensemble (BE), logistic model tree (LT), kernel support vector machine (k-SVM), and k-nearest neighbour (KNN) are the four algorithms used in this study for flood zoning in Jeddah City, Saudi Arabia. The 141 flood locations have been identified in the research area based on the interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…Jaber et al [59] also showed the efficacy of remote sensing precipitation in rainfall-runoff modelling in Iraq. Studies in the nearby region also showed the applicability of satellite rainfall in hydrological applications in Jordan [60], Iran [61], Saudi Arabia [62,63], and Turkey [64].…”
Section: Discussionmentioning
confidence: 95%
“…Jaber et al [59] also showed the efficacy of remote sensing precipitation in rainfall-runoff modelling in Iraq. Studies in the nearby region also showed the applicability of satellite rainfall in hydrological applications in Jordan [60], Iran [61], Saudi Arabia [62,63], and Turkey [64].…”
Section: Discussionmentioning
confidence: 95%
“…However, the significance of models in various operational measures for hydrometeorological disasters has been delineated in the literature. Examples include the application of 2D models (Abdrabo et al, 2020), hydrodynamic models (Chen et al, 2021), statistical models (Lee et al, 2020), decision-making models (Cabrera and Lee, 2019;Taromideh et al, 2022), and machine-learning models (Pourghasemi et al, 2021;Al-Areeq et al, 2022;Li et al, 2022). Despite their ability to simulate flood susceptibility, these models exhibit several limitations, resulting in errors in their application and necessitating calibration stages in different regions.…”
Section: Challenges Of Scenario-based Flood-prone Mapping Model In Th...mentioning
confidence: 99%
“…To evaluate a multiclass classification, the instances correctly and incorrectly classified for each category must be displayed in a very well-organized tabular representation called a confusion matrix of the predicted class labels against the actual class labels (Table 6). The classification product and associated validation sample can be cross-tabulated to determine a variety of metrics, such as overall accuracy (15), class producers' accuracy (16), class users' accuracy (17), and kappa statistic (18)…”
Section: Multiclass Classification's Accuracy Assessmentmentioning
confidence: 99%
“…This was the case in the study of Shreevastav et al [15], which adopted the same approach to assess flood risk modeling in the lower Bagmati river region of Eastern Terai, Nepal, using the ML model of MaxEnt. Moreover, Al-Areeq et al's [16] research used a logistic model tree (LT), a Bagging ensemble (BE), k-nearest neighbors, and a kernel support vector machine to map Jeddah, Saudi Arabia's flood vulnerability. In Karachi, Pakistan, by combining a novel set model of Multi-Layer Perceptron, Support Vector Machine, and Logistic Regression (LR), which additionally assesses influencing variables, Yaseen et al [17] created a flood susceptibility map.…”
Section: Introductionmentioning
confidence: 99%